ANALISIS PENYERAPAN TENAGA KERJA PADA INDUSTRI KECIL (Studi Kasus di Sentra Industri Kecil Ikan Asin di Kota Tegal) - Diah Nur Fadliilah; Hastarini Dwi Atmanti (Universitas Diponegoro, 2012)
ABSTRACT Job opportunity is one of indicators to assess economic development. However, the recruitment of worker still not able overcomes unemployment. The development of small industries will help overcoming unemployment because small industries used technology of labor intensive. Tegal occupied the first job seeker in Central Java with job seeker at 14,22% of the total labor. The highest business unit of small industries in Tegal is salted fish industry. The research uses multiple linear regression (Ordinary Least Square) to analyze the effect of wages, productivity, and working capital for recruitment of worker on salted fish industry in Tegal. The results showed the influence wages to the recruitment of worker obtained t value at -0,717< t table 1,671, it’s indicate that the wages have negative effect on recruitment of worker. The result significance test at 0,476 ˃ 0,05 (α = 5%), it’s shows that wages have no significant effect on the recruitment of worker. The results showed the influence productivity to the recruitment of worker obtained t value at -8,148 > t table 1,671, it’s indicate that the productivity have negative effect on recruitment of worker. The result significance test at 0,000 < 0,05 (α = 5%), it’s shows that productivity have significant effect on the recruitment of worker. The results showed the influence working capital to the recruitment of worker obtained t value at 13,698 > t table 1,671, it’s indicate that the working capital have positive effect on recruitment of worker. The result significance test at 0,000 < 0,05 (α = 5%), it’s shows that working capital have significant effect on the recruitment of worker. The simultaneous test result showed that F value 128,454 > F table 2,76 with significance at 0,000 < 0,05 (α = 5%), it’s mean that wages, productivity, and working capital have simultaneously significant effect on the recruitment of worker.